Integrated Omics Approaches in Meat Science Research : 10.5958/2581-6616.2020.00014.6 - Ramanathan, Ranjith; Nair, Mahesh N.; Kiyimba, Frank; Denzer, Morgan L.; Hearn, Katheryn; Price , Taylor; Mafi , Gretchen G. (Journal of Meat Science, 2020)
Meat is a nutrient-dense food, and its quality depends on various factors that range from pre- to post-harvest. Any alteration in the conversion of muscle to meat can impact product quality and consumer acceptance. Hence, elucidating the factors that can influence meat quality such as tenderness, water holding capacity, flavor, and color are essential to understand quality defects, limit meat wastage, and ensure consumer satisfaction. The aspects involved in meat quality changes are complex and interrelated. Hence, traditional wet-laboratory techniques may not be able to provide global changes in biomolecular interactions. In recent years, a systems biology approach utilizing genomics, proteomics, transcriptomics, and metabolomics has been incorporated into basic meat science research to understand the mechanistic basis of meat quality and the potential development of biomarkers. The overall goal of this review is to give an outline of various omics techniques and their application in meat science research.
Keywords: Genomics; Meat quality; Metabolomics; Omics; Proteomics